Hubungan Antara Tingkat Kesibukan Orang Tua dan Kecenderungan Memilih Teman Sebaya dalam Pengembangan Akhlak Siswa Madrasah Ibtidaiyah - Khotimah, Khusnul; Wahyuningsih, Retno (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2020)
This study is aimed to know the relation between parents’ activity level and students’ tendency to select peers on students’ morals. This study is quantitative in nature with multicorelation approach. Samples are the 63 fifth graders of MI Muhammadiyah Waru Baki Sukoharjo. Data were analyzed using uses a single and multicorelation analysis. Results show that the first hypothesis is proven that there is a negative relation between parents’ activity level with students’ moral, meaning that the higher parents’ outdoor activity, the lower students’ moral. The second hypothesis indicates that there is a positive relationship between students’ tendency to select peers and students’ morals, therefore the more selective the students select their peers, the better their morals. In addition, the third hypothesis defines that there is a relationship between parents’ activity level and students’ tendency to select peers simultaneously with morals. This finding proves that both students' parents activities and tendency to select peers simultaneously affect moral development.